Massive open online nutrition and cooking course for improved eating behaviors and meal composition. Issue 1 (December 2015) - Adam, Maya; Young-Wolff, Kelly; Konar, Ellen; Winkleby, Marilyn
Abstract Background Behavioral shifts in eating, favoring the increased consumption of highly processed foods over healthier, home-cooked alternatives, have led to widespread health problems. This study reports on the effectiveness of a massive open online course (MOOC), offering integrated nutrition and cooking instruction, for improving eating behaviors and meal composition among course participants. Methods The course, consisting of 47 short (4–6 min.) videos, was offered through Coursera, an open, online learning platform, available to individuals worldwide who have access to the Internet. Beginning in January 2014, participants viewed course videos, completed quizzes and participated in optional cooking assignments, over a 5-week period. Participants were invited to complete optional pre- and post-course surveys assessing their eating behaviors, typical meal composition and perceived barriers to home cooking. McNemar-Bowker tests of symmetry and within subjectt -tests were conducted to evaluate pre-post survey changes in the primary variables measured. Results 7, 422 participants from more than 80 countries completed both pre- and post-course surveys, while 19, 374 participants completed the pre-survey only. Class participants were primarily women in the child-rearing ages (20–49 years of age). There were significant positive changes in eating behaviors and meal composition over time, including an increase in the percentage of participants who reported cooking dinner at home using mostly fresh ingredients 5–7 times in the previous week (63.4 % to 71.4 %), and who felt that yesterday's dinner was very/extremely healthy (39.3 % to 56.4 %) and enjoyable (55.2 % to 66.7 %) (allp values < .0001). Conclusions Integrated nutrition and cooking courses, delivered via open online learning platforms, offer a free and flexible venue for reaching adults worldwide and have the potential to catalyze powerful behavioral shifts that align well with efforts to improve eating behaviors and meal composition.